Reducing periprosthetic joint infection: what really counts? - Solarino, Giuseppe; Abate, Antonella; Vicenti, Giovanni; Spinarelli, Antonio; Piazzolla, Andrea; Moretti, Biagio (Joints, 2015)
Periprosthetic joint infection (PJI) remains one of the most challenging complications after joint arthroplasty. Despite improvements in surgical techniques and in the use of antibiotic prophylaxis, it remains a major cause of implant failure and need for revision. PJI is associated with both human host-related and bacterial agentrelated factors that can interact in all the phases of the procedure (preoperative, intraoperative and postoperative). Prevention is the first strategy to implement in order to minimize this catastrophic complication.The present review focuses on the preoperative period, and on what to do once risk factors are fully understood and have been identified.
Keywords: periprosthetic infection; risk factors; preoperative prevention